Bioinstrumentation - Veerakumari L (Chennai : MJP Publishers, 2006)
Bioinstrumentation deals with the instrumentation techniques and principles used for measuring physical, physiological, biochemical and biological factors in man or other living organisms. This book provides a comprehensive knowledge about the basic principles and applications of the tools and techniques generally used in biology and also those used in the growing field of molecular biology. This book will prove to be a dependable reference book for students and teachers of biological sciences.
Includes References 545-548p. and Index 549-556p.
Keywords: Bioinstrumentation; Chemistry; Nano technology; Nano science